Design of Software for User Services in UIC Gateway - WANG Meilan; SHEN Ping; NIE Xiaobo; WANG Lide; YAN Xiang (机车电传动)
The whole procedure how user services allow a remote or a local user to access or control the gateway in UIC gateway was presented, also a software realization solution for receiving call-messages, dealing with user services and producing reply-messages was provided. Function-dealing software was provided for every user service. At last the solution was verified in UIC gateway .